Moderate and vigorous physical activity patterns among marijuana users: Results from the 2007–2014 National Health and Nutrition Examination Surveys. (1st September 2017) - Vidot, Denise C.; Bispo, Jordan B.; Hlaing, WayWay M.; Prado, Guillermo; Messiah, Sarah E.
Highlights: The prevalence of physical activity is lower among marijuana users. Marijuana users have lower odds of moderate physical activity than never users. As frequency of marijuana use increased, time spent on physical activity decreased. Abstract: The relationship between marijuana use and recreational physical activity has yet to be explored in the United States. Our aim was to examine this relationship in a population-based sample of 20-to-59-year olds (N = 12, 618) using 2007–2014 National Health and Nutrition Examination Surveys. Marijuana use was categorized as never (reference group), past (previously but not within the last 30-days), and current ( > 1 day in the last 30-days) use. Current users were further categorized based on frequency of use (light, moderate, and heavy users). Physical activity was self-reported as moderate (small increase in heartrate/breathing for >10 min; MPA) and vigorous (large increase in heartrate/breathing for >10 min; VPA). Adjusted odds ratios (AOR) for the relationship between marijuana use and physical activity were estimated via logistic regression models. The majority of the overall sample reported either past (40.5%) or current (12.6%) marijuana use. Marijuana users had a lower prevalence of moderate physical activity than never users (current: 51.9%, past: 50.4%, never: 55.3%, p = 0.001). Current (66.8%) and past (67.9%) marijuana users also had a lower prevalence of vigorous physical activity than never users (71.9%, p = 0.001). Current and past users had lower odds of recreational MPA (current user AOR: 0.66, 95% CI: 0.50–0.87; past user AOR: 0.78, 95% CI: 0.62-0.98) than never users. As the frequency of marijuana use increased, time spent on MPA decreased. Results suggest that current and past marijuana users were less likely to report recreational MPA than never users. Future studies should examine the potential mechanisms and temporality of this relationship.